Identifying inadequate response among patients with ankylosing spondylitis and psoriatic arthritis prescribed advanced therapy in a real-world, commercially insured adult population in the USA - Hunter, Theresa; Grabner, Michael; Birt, Julie; Isenberg, Keith; Shan, Mingyang; Teng, Chia-Chen; Wu, Jianmin; Griffing, Kirstin; Lisse, Jeffrey; Curtis, Jeffrey R. (Clinical rheumatology, 2022)
Objective This study aimed to assess treatment patterns and frequency of inadequate response associated with advanced therapy initiation among patients with ankylosing spondylitis (AS) and psoriatic arthritis (PsA) in the USA. Methods Adult patients with AS or PsA who initiated advanced therapy were identified from the HealthCore Integrated Research Database®. Inadequate response to advanced therapies (tumour necrosis factor inhibitors [TNFi] and non-TNFi biologics) was identified using a claims-based algorithm. Factors influencing inadequate response were assessed using multivariable logistic regression. Results In total, 646 patients with AS, and 1433 patients with PsA were evaluated. Among patients with AS (mean age, 43 years; male, 58%), 93% patients initiated TNFi, and 69% of patients had inadequate response. In patients with PsA (mean age, 49 years; male, 47%), 67% initiated TNFi, and 77% had inadequate response. Low adherence was the main predictor of inadequate response in patients with AS (56%) and PsA (63%). Inadequate responders were more likely to be female (odds ratio [OR] 2.05 for AS and 1.37 for PsA). Prior exposure to TNFi was associated with 3.89- and 2.14-fold greater odds of inadequate response in both AS and PsA patients, respectively, while patients using methotrexate were less likely to have inadequate response (OR 0.48 for AS and 0.72 for PsA; all p < 0.05). Conclusions Over 69% of patients with AS and 77% of patients with PsA had inadequate response to their index advanced therapy during 1 year after initiation. Health plan claims data appear useful to classify inadequate responders in AS and PsA. Key Points • Estimating inadequate response to advanced therapies and identifying factors associated with this outcome using claims data could improve treatment outcomes in AS and PsA. • In a sample of commercially insured US patients, over 69% of patients with AS and 77% of patients with PsA had inadequate response to their index advanced therapy during 1 year after initiation. Patient characteristics such as sex and prior therapy use were predictive of inadequate response to advanced therapies. • Health plan claims data appear useful to classify inadequate responders in AS and PsA and identify factors associated with this outcome.